A BRIEF STUDY OF VARIOUS SLASIL E TASWWUF IN KASHMIR: AN ANALYTICAL STUDY - Bashir Ahmad Malik; Dr. Maqsood Ur Rehman; Dr. Abdul Naseer; Aziz Ahmad; Dr. Zia Ullah; Dr. Asad Ullah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Sufism has been a movement in Kashmir which has created confusion in the spiritual life of its people. Sufism in Kashmir reflects the practices of Kashmiris, Pundits and Muslims. Here Sufism is not like other Sufi traditions as it exists in different parts of Central Asia and South Asia. Sufism in Kashmir replicates the practices of Kashmiri, Pundits and Muslims. Kashmir became the foundation of Islam through his teachings. Besides, Kashmir has had a large number of its own Sufis who have been connected with different sects of Sufism. These Sufis belonged to all the sects of Sufism. Besides, the local spiritual lineage of Kashmir has also been famous here which is called Rishi lineage made the cradle of Islamic civilization. These Sufis concreted the way for the Islamic Revolution in the history of Kashmir through their composition and compilation services. The arrival of these sequences in Kashmir and their historical background will be defined in this research article.